When Feelings Become Facts: The Evidentiary Crisis in Malaysia’s Cyber Laws - Mawi, Hasshahari Johari; Rajamanickam, Ramalinggam; Zahir, Mohd Zamre Mohd; A.Kadir, Nadhilah; Saad, Hasbollah Mat (Journal of Posthumanism, 2025)
Section 233(1)(a) of Malaysia's Communications and Multimedia Act 1998 criminalizes transmitting offensive (jelik), indecent, false, menacing, or offensive communications with intent to annoy, abuse, threaten, or harass. However, the term "offensive" remains ambiguously defined, relying on subjective societal norms and emotional interpretations, leading to inconsistent legal applications. This ambiguity complicates enforcement, as prosecutors must prove both the offensive nature of the content and the accused's malicious intent, while the accused face the additional challenge of rebutting Section 114A of the Evidence Act 1950, which presumes their liability for online content. The lack of clear judicial guidance exacerbates these issues, underscoring the need for legislative or precedential clarity to balance free expression with protection against digital harassment. This writing aims to highlight the current legal situation in Malaysia and the approach taken by criminal trial courts in addressing the evidentiary crisis surrounding Section 233 of Communications and Multimedia Act 1998. The study employs a qualitative research methodology, analyzing primary and secondary legal sources, including case law and statutory provisions, to assess the challenges in defining and proving "offensive" conduct. Key findings reveal significant inconsistencies in judicial interpretations, with courts relying on subjective societal standards and emotional responses to determine offensiveness. The study also identifies the disproportionate burden placed on the accused due to the presumption of liability under Section 114A of the Evidence Act 1950. To address these issues, this writing recommends legislative amendments to provide clear definitions of "offensive" conduct, grounded in Malaysia’s socio-cultural context. Additionally, it calls for judicial guidelines to standardize the application of Section 233, ensuring fairness and predictability in enforcement. These measures would enhance legal certainty while safeguarding fundamental rights to free expression and protection from digital harassment.